High resolution incremental stress testing of crushable granular materials - Ciantia Matteo; Arroyo Marcos; Gens Antonio (E3S Web of Conferences, 2019)
The incremental behaviour of crushable sands is investigated by means of a Discrete Element Method (DEM) based analogue. The DEM sample is subjected to a comprehensive set of small stress perturbations in the triaxial plane in order to identify the basic mechanisms contributing to the corresponding strain response. Three contributions to incremental strains are distinguished: elastic, plastic-structural and plastic-crushing. The behaviour observed appears to be consistent with the classic tenets of elasto-plasticity. It is also shown that high resolution probing is required to identify significant features such as elastic anisotropy and irreversible effects on the tangent bulk and shear moduli. As a consequence, computational efficiency is therefore a must for numerical studies of incremental response.